Lactulose with synergists supplementation improving a health of chicks and reducing the environmental burden in poultry industry - Ivan Fiodorovich Gorlov; Marina Ivanovna Slozhenkina; Daria Aleksandrovna Mosolova; Lyudmila Viktorovna Khoroshevskaya; Zoya Borisovna Komarova; Vladimir Nikolaevich Nikulin; Evgeniya Aleksandrovna Struk; Aleksey Petrovich Khoroshevsky; Elena Yurievna Anisimova (Journal of Advanced Veterinary and Animal Research, 2024)
Objective: The study aims to understand the effect of new antibiotic-substituting supplements in feeding chickens of the Hisex Brown cross in industrial conditions. Materials and Methods: A total of 216 hatched chicks were randomly selected and distributed into Control, Test I, and Test II groups, with 3 replicates of 24 birds in three treatments. Results: At the end of the experiment, BW of T1/T2 birds was higher by 6.12% (p [J Adv Vet Anim Res 2024; 11(2.000): 429-438]